1999
DOI: 10.1074/jbc.274.32.22785
|View full text |Cite
|
Sign up to set email alerts
|

AP180 and AP-2 Interact Directly in a Complex That Cooperatively Assembles Clathrin

Abstract: Clathrin-coated vesicles are involved in protein and lipid trafficking between intracellular compartments in eukaryotic cells. AP-2 and AP180 are the resident coat proteins of clathrin-coated vesicles in nerve terminals, and interactions between these proteins could be important in vesicle dynamics. AP180 and AP-2 each assemble clathrin efficiently under acidic conditions, but neither protein will assemble clathrin efficiently at physiological pH. We find that there is a direct, clathrin-independent interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 56 publications
3
105
0
Order By: Relevance
“…Furthermore, we suggest that the reason for AP-mediated assembly of clathrin to be inefficient at physiological pH is to allow assembly to be regulated by other proteins, such as Eps15. This is consistent with previous studies indicating that the AP180-AP2 interaction also serves to facilitate cooperative clathrin assembly at physiological pH (32).…”
Section: Figsupporting
confidence: 82%
“…Furthermore, we suggest that the reason for AP-mediated assembly of clathrin to be inefficient at physiological pH is to allow assembly to be regulated by other proteins, such as Eps15. This is consistent with previous studies indicating that the AP180-AP2 interaction also serves to facilitate cooperative clathrin assembly at physiological pH (32).…”
Section: Figsupporting
confidence: 82%
“…In fact, there is already some experimental evidence to support this idea. Complexing AP-2 with AP180 leads to enhanced clathrin assembly activity (20), and we have previously shown that AP-2 recruitment to the central DPW region (residues 249 -401) of epsin 1 augments clathrin binding mediated by the epsin sequence 257 LM-DLADV (15). Here, we further characterized this epsin se-quence and a related clathrin-binding sequence from amphiphysin, PWDLW (21).…”
mentioning
confidence: 91%
“…Each protein has a PI(4,5)P 2 binding domain and both bind to AP-2 and clathrin. Both AP-2 and CALM/AP180 are able to stimulate clathrin assembly by them selves, but the interaction between AP-2 and CALM/AP180 increases the ability of AP-2 to assemble clathrin (Hao et al, 1999). ß-arrestin is another sorting adaptor involved in clathrin-mediated endocytosis.…”
Section: Additional Adaptor Proteins In Clathrin-mediated Endocytosismentioning
confidence: 99%